A Simple Application Program Interface for Saving Java Program Data on a Wiki. (20th February 2012) - Yamanoue, Takashi; Oda, Kentaro; Shimozono, Koichi
Abstract : A simple application program interface (API) for Java programs running on a wiki is implemented experimentally. A Java program with the API can be running on a wiki, and the Java program can save its data on the wiki. The Java program consists of PukiWiki, which is a popular wiki in Japan, and a plug-in, which starts up Java programs and classes of Java. A Java applet with default access privilege cannot save its data at a local host. We have constructed an API of applets for easy and unified data input and output at a remote host. We also combined the proposed API and the wiki system by introducing a wiki tag for starting Java applets. It is easy to introduce new types of applications using the proposed API. We have embedded programs such as a simple text editor, a simple music editor, a simple drawing program, and programming environments in a PukiWiki system using this API.